Analysis of multiple isoenzyme expression among twenty-two species of Mycoplasma and Acholeplasma. - O'Brien, S J (1981)
Crude extracts of triple-cloned, purified cultures of 22 species of Mycoplasma and Acholeplasma were examined for expression of 21 isozyme systems routinely used to type mammalian cells. Nine previously described enzymes (purine nucleoside phosphorylase, adenylate kinase, dipeptidase, esterase, glyceraldehyde-3-phosphate dehydrogenase, glucose phosphate isomerase, glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase, and superoxide dismutase) and three enzymes not previously reported in mycoplasma (triose phosphate isomerase, inorganic pyrophosphatase, and acid phosphatase) were detected in some or all of the species examined. These findings provide new information on the enzymatic expressions of these organisms. Three of the isozyme systems (superoxide dismutase, glucose-6-phosphate dehydrogenase, and 6-phosphogluconate dehydrogenase) were present in Acholeplasma species but not in any Mycoplasma species. The characteristic pattern of electrophoretic mobility of the 12 isozyme systems also provides a useful biochemical property for identification, characterization, and classification of these mycoplasmas. Mycoplasma isozyme expression for seven of the enzymes were readily detected in various infected-cell culture lines by using either cell extracts or concentrated cell culture fluids. Mycoplasma-specific enzymes found in infected-cell extracts had the same electrophoretic mobility patterns as enzymes obtained from broth-grown mycoplasmas of the same species. Expression of homologous mammalian enzymes was not detectably altered by infection with mycoplasmas.